Improved retention performance after variable practice comes in line with an increased alpha band power over the prefrontal cortex - Thürer, B.; Stockinger, C.; Stein, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: It is widely accepted that variable practice enhances the motor performance after a period of consolidation (Shea & Morgan, 1979). This effect could be explained by cognitive demanding processes in the prefrontal cortex which potentiate subsequent memory consolidation (Kantak et al., 2010). However, it is still unknown which neural processes lead to the enhanced motor performance. The aim of this study was to investigate the electrophysiology of learning related frequency bands over prefrontal areas in a motor adaptation task under variable practice conditions. Methods: Subjects (n=24) were equally distributed in two groups (blocked, random) and performed goal-directed arm reaching movements handling a robotic device. Both groups performed a similar schedule over two consecutive days containing a familiarization and training block on day 1 (each 148 trials) and a retention block on day 2 (32 trials). During the training block, subjects` movements were perturbed by a viscous curl force field with three gradations (10, 15, 20 Ns/m) in either blocked or random order. In the retention block, the force field was consistent at 15 Ns/m. We recorded hand-trajectories to quantify subjects` motor performances while adapting to the force field. Electroencephalography (EEG) was collected using 32 active-electrodes. After artifact correction, the percentage power of theta (4-7 Hz), alpha (8-13 Hz), and gamma (60-85 Hz) bands as well as theta-gamma phase-amplitude coupling (Canolty et al., 2006) were computed during movement execution. Statistical analyses were done using permutation testing. Results: The kinematic data exhibited a significant interaction (p=.037; pEta2=.18) between time (training, retention) and group revealing an increased performance improvement for the random compared to the blocked group. Furthermore, EEG alpha band power during movement execution showed a significant time and group interaction (p=.047; pEta2=.17) indicating an increased alpha power during memory retrieval for the random group. Discussion: This is the first study investigating the consolidation of variable practice in a force field adaptation task using EEG. The results show a positive effect of variable practice on motor performance which comes in line with an increased alpha band power over prefrontal areas. This supports previous hypotheses (Kantak et al., 2010) that the benefit of variable practice is facilitated by cognitive processes in the prefrontal cortex.